2021
DOI: 10.1111/desc.13213
|View full text |Cite
|
Sign up to set email alerts
|

The influence of attentional biases on multiple working memory precision parameters for children and adults

Abstract: Working memory (WM) improves dramatically during childhood but what drives this improvement is not well understood. One influential account thus far has proposed a simple increase in storage capacity. However, recent findings have shown that multiple factors, such as differences in the ability to use attention to enhance the maintenance of internal representations, as well as changes in WM precision, also interact in influencing age-related differences in WM capacity. We aimed to examine whether and how the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 106 publications
2
2
0
Order By: Relevance
“…The mean error in the color matching task was only 8.54 for the younger children, 4.76 for the older children, and 3.70 for the adults, respectively. This is similar to previous developmental studies (Burnett Heyes et al, 2012; Shimi & Scerif, 2022).…”
Section: Resultssupporting
confidence: 93%
“…The mean error in the color matching task was only 8.54 for the younger children, 4.76 for the older children, and 3.70 for the adults, respectively. This is similar to previous developmental studies (Burnett Heyes et al, 2012; Shimi & Scerif, 2022).…”
Section: Resultssupporting
confidence: 93%
“…The most vital contribution of the present study is to provide new neurophysiological evidence for an attentional enhancing model of retrospective cues. Behaviorally, we used mixture model to fit behavioral responses and revealed that retrospective attentional cues can enhance target response probability which was consistent with previous studies (34, 35). Furthermore, EEG-based multivariate pattern classification analysis showed that the decoding accuracy of target orientation started to be higher than chance level about 500 ms after the valid retro-cue favoring the target strengthening hypothesis.…”
Section: Discussionsupporting
confidence: 85%
“…Refreshing is assumed to emerge around the age of 7 years old and its efficiency is assumed to increase over time until around 14 years old ( Barrouillet et al 2009 ). Refreshing has been extensively studied in adults (e.g., Barrouillet et al 2011 ; Lemaire et al 2018 ; Loaiza and Souza 2018 ; Oberauer and Lewandowsky 2011 ; Raye et al 2007 , 2008 ; Rey et al 2018 ; Souza et al 2015 ; Vergauwe et al 2014 ; Vergauwe and Langerock 2017 ) and, albeit to a lower degree, in children (e.g., Barrouillet et al 2009 ; Oftinger and Camos 2015 , 2017 , 2018 ; Shimi and Scerif 2015 , 2017 , 2022 ; Tam et al 2010 ; Vergauwe et al 2021 ). However, evidence about attentional refreshing in adolescence is particularly scarce.…”
Section: Introductionmentioning
confidence: 99%